Peran Mahasiswa Asistensi Mengajar Dalam Kegiatan Intrakulikuler Dan Ekstrakulikuler di Man 2 Mataram - hasani, riadhatul; Dinda Annisya, Sukma; Hidayat, Rabiyatun; Lestari Widiantika, Susi; Anida Zulfa, Baiq; Isnaeni, Isnaeni; ayuni, Nur; Masmira, Ade; Lucky Anugrah, Riska; Febrianti, Suhaemi; Fajarli Apriani M, Baiq (Jurnal Pengabdian Masyarakat Sains Indonesia (Indonesian Journal Of Science Community Services), 2024)
Teaching Assistance is one of the programs from Merdeka Belajar Kampus Merdeka or known as MBKM. This program was opened with the aim of providing students with the opportunity to learn by developing themselves outside campus through Teaching Assistance in secondary school level education units under the guidance of field supervisors. The methodology for implementing Teaching Assistance carried out by Mataram University students at MAN 2 MATARAM is the observation method, this method was chosen because the researcher saw the object under study directly. During the implementation of teaching assistance activities at MAN 2 MATARAM, assistant students have played a role and participated in various programs at MAN 2 MATARAM, both academic, non-academic, formal and non-formal, including: Teaching, creating learning tools, participating in administration. are at school, and participate in every activity at school, such as helping and accompanying students in extracurricular activities at school. Overall, the Teaching Assistance activities carried out by Mataram University students went well and both the school, university and students had a positive impact.